2014
DOI: 10.1007/s00213-014-3783-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute escitalopram but not contextual conditioning exerts a stronger “anxiogenic” effect in rats with high baseline “anxiety” in the acoustic startle paradigm

Abstract: The results support the usefulness of both conditioned and non-conditioned startle and freezing to capture an "anxiogenic" influence of SSRIs. Also, they suggest that baseline non-conditioned startle may predict this response in a manner reflecting the clinical situation in the sense that subjects with high baseline "anxiety" are particularly prone to respond with enhanced "anxiety" following acute SSRI administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Our observation that noise bursts, a stimulus more frequently used to elicit startle behaviour, elicit a moderate degree of freezing is in line with previous studies (22,32,33). We suggest this response, which displayed a considerable degree of test-retest inter-individual variation, to be a feasible paradigm for future investigations of the modulation of mild fear responses.…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that noise bursts, a stimulus more frequently used to elicit startle behaviour, elicit a moderate degree of freezing is in line with previous studies (22,32,33). We suggest this response, which displayed a considerable degree of test-retest inter-individual variation, to be a feasible paradigm for future investigations of the modulation of mild fear responses.…”
Section: Discussionsupporting
confidence: 93%
“…The observed MXE‐induced antidepressant‐like effect is not due to alterations in locomotor activity because the same dose of MXE did not enhance locomotor activity. Notably, we showed that a single injection of MXE induces anxiogenic and antidepressant effects, a pharmacological feature that this drug shares with ketamine (da Silva et al, ) and several selective 5‐HT reuptake inhibitors (SSRIs) (Griebel et al, ; Kurt et al, ; Pettersson et al, ). As such, we cannot exclude the possibility that, as reported for SSRIs and other agents that augment 5‐HT signalling, high doses of MXE may elicit an anxiety‐like state during the first few days (or weeks) of use, before anxiolytic effects emerge (Ravinder et al, ; Jonassen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Valcyte − CIE female rats with intact NPCs showed enhanced freezing responses compared to CIE naïve rats and Valcyte + CIE rats during the baseline session that occurred at 72 hours of abstinence. Enhanced freezing during the baseline session is suggested to indicate anxiety-like behavior (Brandao et al , 2008; Pettersson et al , 2015), a phenotype that is demonstrated in female rats after chronic ethanol experience (Getachew et al , 2008). Valcyte prevented the rebound burst in NPCs in CIE female rats and reduced freezing responses during baseline session, demonstrating a role for NPCs generated during early abstinence in anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%